1999
DOI: 10.1038/43448
|View full text |Cite
|
Sign up to set email alerts
|

Leptin reverses insulin resistance and diabetes mellitus in mice with congenital lipodystrophy

Abstract: Congenital generalized lipodystrophy (CGL) is a rare autosomal recessive disorder characterized by a paucity of adipose (fat) tissue which is evident at birth and is accompanied by a severe resistance to insulin, leading to hyperinsulinaemia, hyperglycaemia and enlarged fatty liver. We have developed a mouse model that mimics these features of CGL: the syndrome occurs in transgenic mice expressing a truncated version of a nuclear protein known as nSREBP-1c (for sterol-regulatory-element-binding protein-1c) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
628
5
19

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 939 publications
(680 citation statements)
references
References 14 publications
28
628
5
19
Order By: Relevance
“…Interestingly, transplantation of white adipose tissue from wild-type mice to these lipodystrophic mice leads to an improvement in insulin sensitivity (Kim et al, 2000a). Similar results are observed with leptin administration (Shimomura et al, 1999). In line with these studies, investigations in humans with lipodystrophia revealed that although visceral or peripheral fat were almost absent, these patients developed NAFLD and hepatic insulin resistance (Petersen et al, 2002;Savage et al, 2005).…”
Section: Ectopic Fat Accumulation Promotes Hepatic Insulin Resistancesupporting
confidence: 82%
“…Interestingly, transplantation of white adipose tissue from wild-type mice to these lipodystrophic mice leads to an improvement in insulin sensitivity (Kim et al, 2000a). Similar results are observed with leptin administration (Shimomura et al, 1999). In line with these studies, investigations in humans with lipodystrophia revealed that although visceral or peripheral fat were almost absent, these patients developed NAFLD and hepatic insulin resistance (Petersen et al, 2002;Savage et al, 2005).…”
Section: Ectopic Fat Accumulation Promotes Hepatic Insulin Resistancesupporting
confidence: 82%
“…Previously, we and others have demonstrated that food intake reduction alone was insufficient for improving glucose and lipid metabolism [6,10,12]. It has also been reported that fasting insulin and triacylglycerol levels increased within several days after withdrawal of leptin administration even though the level of food intake remained constant in the patients with lipodystrophy [13].…”
Section: Discussionmentioning
confidence: 92%
“…Given the glucose-lowering action of leptin, we and others have demonstrated that leptin infusion or transgenic overexpression of leptin reverses metabolic abnormalities in different mouse models of lipodystrophy [10,12]. Recently, we and others confirmed that leptin treatment effectively reduces food intake and improves hyperglycaemia, hypertriacylglycerolaemia and fatty liver in patients with lipoatrophic diabetes [13][14][15][16].…”
Section: Introductionmentioning
confidence: 90%
“…This is corroborated by recent clinical and animal investigations that excess as well as complete absence of fat in the body are concomitant with hyperinsulinemia, insulin insensitivity and diabetes. 7,[22][23][24][25][26][27][28] The discovery of insulin in 1922 and the subsequent development of insulin analogs have been the life-saving treatments of hyperglycemia and in delaying or preventing the array of chronic complications of diabetes mellitus. 2,13,[29][30][31] Diabetes, therefore, has traditionally been viewed as an affliction of either lack of or incomplete use of insulin and, consequently, conventional research has focused entirely on improving ways to deliver insulin for precision in attaining glycemic control to simulate the physiological range of blood glucose, necessary to combat the comorbidity cluster of this chronic malady.…”
Section: Introductionmentioning
confidence: 99%